Desejos à margem: fragmentos de memórias homossexuais em São Carlos - Kurashige, Keith Diego (2018)
Through time, notable changes took place in the sphere of homosexual desire. Men who sought to have sexual encounter with other men for sexual purposes from the few available models in their daily lives acquired more social vocabulary, while the communication media like radio, cinema and television were developing. At fast pace, in a short historical gap, the meetings that were mirrored by the local models soon were also mirrored by models coming from other contexts by the media. The AIDS epidemic emerged in this scenario, and acting as a catalyst pumped the representation sphere and thus intensified the presence of homosexuality in speeches, since the disease was at first considered a gay disease, discussions and debates were raised. It was possible, due to this tragic context, to create both positive and negative images in the media, which caused the start of new ways of identification and alternative ways to have those meetings. Digital media emerged soon after, and it was at first one of many refuges for those trying to circumvent social barriers. The contact with communication media became more intense through accessibility, and the representations that emerged in it began to take a leading role in the social vocabulary of seeking love / sexual partners, making subjects increasingly connected to the idealized models. This history has contextual specificities which I unraveled from the memory of the research subjects that helped me rebuild an alternate history of the city of São Carlos.